Análisis comparativo entre las tecnologías de IA Amazon y Google Assistant en la integración y control de dispositivos inteligentes para el hogar. - Real Yépez, Solanlly Vanessa (2024)
The world is in an era where smart technology has become a part of our daily lives and continues to evolve. Most people can use voice assistants on their smartphones, as here this technology is pre-installed on most devices. The current boom in the use of virtual assistants is largely due to the great popularity of smart speakers. When we talk about virtual assistants, we cannot fail to mention these smart speakers that are most used in the home. Smart speakers are based on artificial intelligence, and artificial intelligence is a virtual assistant that we can also have on our mobile phone. Smartphones can be used for many different tasks where the interaction is tactile, vocal or joint, but smart speakers have to be voice, except for models with a screen.